Exploring Students’ Experiences of Virtual Learning Environment for Art History Classroom - Park, Jiyeon; Sohn, Sooyun (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
During the Covid 19, students and instructors experienced double-way synchronization distance classes. Recently, the metaverse was drawn much attention to the online virtual world as a channel for social interaction. It has received renewed interest as a new method of surmounting the limitations of external activities after the pandemic. A few studies have focused on the usability of metaverse in a classroom, but no attention was paid to its applicability to Art History as well as to the higher level of education. In order to compensate for the limitations of two-way synchronized remote learning in university art history classes, Gather.Town was adopted as a metaverse platform in both Western modern art history classes and art history methodology classes. In this study, we surveyed and interviewed students who used both WebEx and Gather.Town. This study examines students’ experiences in accessibility, social presence, convenience of interaction, interest and immersion, and satisfaction when the students use the metaverse platform, Gather.Town. The examination of this study confirms that the virtual space of metaverse was more helpful in making students feel a sense of presence, interaction, and engagement than WebEx and demonstrates the possibility of this platform as a sustainable and valid tool in Art History Education.